Antropologiczny wymiar życia społeczno-gospodarczego w świetle współczesnej polskiej myśli teologiczno-moralnej - Zadroga, Adam (Annales. Etyka w Życiu Gospodarczym, 2008)
The Catholic Church’s Social Teaching dealing with mankind is interested in the person and theirway of progressing in the world. As John Paul II stated, Catholic Social Teaching “belongs [...] tothe field [...] of theology, particularly moral theology” (SRS 41; CA 55). Polish moralists in the area ofsocial moral theological studies undertake the issue of economic-social life, and in particular itsanthropological dimension. Moral reflections from the theological point of view allow for an integralgrasping of the involvement of the person in the life of society.The goal of the presented report is to show an integral concept of the person as the fundamentaldimension of social-economic life. The principle source of this work is comprised of views presented onthe given topic by the nation’s moralists during over a dozen lately held yearly meetings of the Sectionof Polish Moral Theologians. The contents of the report are divided into three parts: (1) the integratedvision of the person as the principle element of evaluating the social-economic order; (2) threats tothe human person in the context of contemporary social-political life and (3) pointing to ways ofovercoming these threats.